Operational Bottlenecks and Challenges of Slaughterhouse Workers in Tamale Metropolis Ghana - Asare, Solomon Ossom; Gyasi, Prince Kwadwo; Hassan, Okrah George; Abiodun, Ogwa Oluwafunmike (Darul Yasin Al Sys, 2025)
This study focused on assessing operational bottlenecks and challenges of slaughterhouse workers in Tamale metropolis Ghana. The research aims to provide insights into the distribution and intensity of various activities near within the abattoir, this including. Access to potable water for the washing of carcasses after processing is a challenge, Difficulty with disposal of solid waste which is far away from the abattoir, Availability drainage for liquid waste management in the slaughterhouse, the slaughterhouse is not shielded sufficiently to prevent the entry of pests, and Non-availability of fumigation activities as a pest control measure as well as Non-availability of separate areas for skinning /dehairing process of the carcass. The study aims to evaluate the operational bottlenecks and challenges of slaughterhouse workers in Tamale metropolis Ghana. The research employed several spatial analysis techniques, such as density mapping, and hotspot analysis, to assess the spatial patterns and relationships between the abattoir and its surrounding areas. The spatial analysis identified potential issues such as the presence of critical infrastructure in close proximity to the slaughterhouse. Thus, solution to those challenges.